IL-6 production through repression of UBASH3A gene via epigenetic dysregulation of super-enhancer in CD4+ T cells in rheumatoid arthritis - Kaoru Yamagata; Shingo Nakayamada; Tong Zhang; Anh Phuong Nguyen; Naoyuki Ohkubo; Shigeru Iwata; Shigeaki Kato; Yoshiya Tanaka (BMC, 2022)
Abstract Background Rheumatoid arthritis (RA) is associated with immune dysfunction. UBASH3A as a negative regulator of T cell receptors (TCRs) signaling is a susceptible factor in RA. The aim of this study was to determine the role of UBASH3A in RA pathogenesis, by assessing the role of super-enhancer (SE) in the control of UBASH3A expression in CD4+ T cells and the contribution of the latter in proinflammatory cytokine production in patients with RA. Methods UBASH3A mRNA and protein levels were quantified by PCR and western blotting, respectively. The cells were treated with a locked nucleic acid to inhibit enhancer RNA (eRNA) expression. Chromatin immunoprecipitation was used to identify the factors recruited to UBASH3A loci displaying SE architecture. CD4+ T cells were transfected with UBASH3A plasmids, and cytokine levels were measured by a cytometric bead array. Results UBASH3A was extracted as a RA susceptibility gene associated with SNPs in the SEs that are highly expressed in CD4+ T cells by in silico screening. UBASH3A mRNA and protein expression levels were lower in CD4+ T cells of RA patients than in the control. eRNA_1 and eRNA_3 knockdown reduced UBASH3A mRNA levels. RA patients exhibited accumulation of BTB and CNC homology 2 (BACH2), the silencing transcription factor, at the UBASH3A loci in CD4+ T cells, but not the SE-defining factor, mediator complex subunit 1 (MED1)/bromodomain 4 (BRD4). However, opposite changes were observed in the control. Stimulation of TCRs expressed on CD4+ T cells of RA patients resulted in interleukin (IL)-6 production, while UBASH3A over-expression significantly inhibited the production. Conclusions In RA, transcription of UBASH3A is suppressed via epigenetic regulation of SE in CD4+ T cells. Low UBASH3A levels result in excessive TCR signal activation with subsequent enhancement of IL-6 production.